The Arches House in the history of Brasilia cinema - da Silva Almeida, Sarah (2020)
Brasilia was projected on the dry soil of the cerrado and built by the hands of those who saw beyond today. It was perpetuated by the lenses that captured the light of the capital and the sweat that dropped on the floor. This article proposes a reflection on this relationship: architecture and cinema, in the beginning of Brasilia. To achieve this, it will focus on a specific work: the Nivaldo Borges Residence, whose construction began in 1972. The Arches House, as it is popularly known, has a remarkable history, designed by the architect Lelé, it is also famous for its link with the cinematic history of the Federal Capital. By addressing issues related to the importance of preserving the memory of Brasilia cinema and the places that still exist and help to perpetuate it, symbolizing the link between cinema, architecture and memory, it is hoped that this work will bring out part of the value that this iconic city building has. To this end, its history, values ”‹”‹and connection with the diffusion of cinematographic art are recorded. To perform the work were carried out: literature review, construction visits and interviews with the current owners, direct descendants of the original builder.